Management practices and perception of waste face masks in university hostels and halls and potential risks: Recommendations for future preparedness - Douti Biyougue Nang; Ebenezer Ebo Yahans Amuah; Arkoh Abena Jennifer; Samuel Kojo Abanyie; Kwame Anokye; Peace Ankor (Green Technologies and Sustainability, 2025)
The COVID-19 pandemic significantly increased the use of personal protective equipment (PPE), particularly face masks, which led to considerable waste management challenges. This study examined the management practices, perceptions, and potential risks associated with waste face masks among students at C. K. Tedam University of Technology and Applied Sciences. Data were collected from 150 respondents using semi-structured questionnaires and a convenience sampling approach. The results showed that 67% of students used surgical masks, while 33% used fabric masks. Daily mask usage indicated that 92% of the students used between 1–5 masks, while 8% used 6–10 masks. Also, 76% of respondents disposed of their masks with general waste, while 24% separated them before disposal. Disposal methods included burning (48%), dumping at designated sites (22%), and using public waste containers (30%). Also, 73% of the respondents believed improper disposal posed health risks, and 42% recognized potential environmental harm, such as pollution. In assessing agreement on waste management practices using a seven-point Likert scale, 51.3% strongly agreed that managing face mask waste at the hostel level should be encouraged, while 24.0% agreed, and 13.3% were neutral. Irregular waste collection (mean score: 4.27) was identified as a key barrier to proper disposal. The findings underscored the need for interventions, such as the provision of designated PPE waste bins, awareness campaigns to educate students on proper disposal practices, and improvements in waste collection frequency. These measures were crucial for reducing health and environmental risks and for enhancing preparedness for future public health emergencies.